Optimal spatial processing effectiveness indexes calculation for fixed wireless communication system radiolink. (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2013)
Introduction. The effectiveness of the theoretical results of optimal spatial processing ot-wo radio signals at the receiving side of wireless communication system with two radio signals which operating simultaneously on the same frequency and same polarization using the curvature of the electromagnetic waves phase front produced on the basis of analysis of attenuation signal coefficient, interference rate suppression and signal-to-noise ratio are shown. Formulation of the problem. Initial data and wireless communication system configuration for research are described. Simulation results. Signal-of-interest attenuation index and signal-to-interference plus noise parameter calculation for sparse linear antenna array (SLAA) are presented. Conclusions. There is relationship between parameters of transmit and receive SLAA for optimal spatial signal processing in the wireless communication system.